Facile Soft Chemical Synthesis and Physical Characterization of Aluminum Doped CeO2 Nanoparticles for Multiple Applications - Chidaraboyina, Swathi; Samson Nesaraj, A. (Asian Journal of Chemistry, 2021)
In this work, a simple facile preparation of Ce1-xAlxO2-δ (where x = 0, 0.1, 0.2, 0.3, 0.4 and 0.5) nanoparticles by chemical synthesis route is reported. In the preparation, appropriate quantities of metal nitrate salts were dissolved in water alongwith required amount of sodium hydroxide as precipitant. The resultant precipitate mixture [Ce(OH)3 + Al(OH)3] was washed with water, filtered, dried and heat treated to get the phase pure Al doped CeO2 nanoparticles. The synthesized oxide materials were characterized by XRD, FTIR, particle size analysis, SEM and EDAX to understand their structural, functional and particle properties. The XRD patterns revealed the presence of cubic (FCC) crystalline structure in the samples. The presence of Al-O and Ce-O stretching mode of vibration was confirmed by FTIR analysis. The particle size of the materials was found in the range of 117.23 to 257.06 nm. Presence of nano and micron sized grains was noticed by SEM photographs. EDAX confirmed the presence of appropriate atomic weight percentage of elements in the samples. The results suggested that the prepared Al doped ceria nanoparticles can be useful in several applications.